An exact solution for vibro-acoustic response of MEE composite plate. (October 2022) - Arunkumar, M.P.; Bhagat, Vinod; Swetha, S.; Geng, Qian; Pitchaimani, Jeyaraj; Li, Yueming
Abstract: To the best of our knowledge, this is the first endeavor to present an exact solution to predict vibro-acoustic characteristics of Magneto-electro-elastic (MEE) composite plate. The transverse and in-plane fields are considered based on thin-plate conditions. The variation of electric and magnetic potentials is determined according to electromagnetic boundary conditions and the Maxwell equation. The stress resultants and mass inertias are used in Hamilton's principle to generate the governing equation. Here the mathematical formulation is developed using third-order shear deformation theory. Also in this work, the dynamic displacement responses are provided by finding five undetermined mode coefficients relevant to u, v, w, ϕ x, and ϕ y to predict forced vibration response. The forced vibration response obtained based on the developed governing equation is used to calculate the acoustic characteristics using the Rayleigh integral. The effect of magnetic and electric potential is shown in the acoustic responses. From the results, it is understood that the acoustic responses are highly influenced by the applied magnetic and electric potential. The radiation efficiency of the MEE plate did not show any variations in the lower frequency and it shows the variation near the resonant frequencies on the application of electric and magnetic potential. Highlights: This is the first-ever work on predicting vibro-acoustic characteristics of a MEE Plate. An exact solution for a vibro-acoustic response of MEE composite plate is derived. The acoustic response is significantly influenced by applied electric and magnetic potential.